INTERNET FINANCIAL REPORTING: THE CASE OF PHILIPPINE BANKS - Briones, Jesus P.; Cabrera, Doringer P. (JURNAL AKUNTANSI DAN AUDITING, 2016)
The purpose of this research is to evaluate the extent of internet financial reporting (IFR) of Philippine banks.Â  Used as samples were top commercial banks and thrift banks operating in the country considering their total assets as of March, Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â 2012 as published by the Bangko Sentral ng Pilipinas in its website. Financial information in the websites of the sampled banks were evaluated during the third quarter of 2012.Â  The study revealed that the quality and extent of IFR of Philippine commercial banks is â€œaverageâ€ based on their IFR index score of 44.50 while thrift banks posted a below average IFR index score of 21.56 resulting to a highly significant difference between bank types. Among the four evaluation criteria used, the subject-banksâ€™ content disclosure provides the highest percentage contribution to their IFR index scores as this is the main focus of their financial reporting. Among the components of content disclosure, corporate information, chairmanâ€™s report and the auditorâ€™s report emerged as the top three often included in the financial disclosure of the subject-banks while vision statement and press release are the components often updated by both bank types in their websites with the commercial banks notably updating more frequently compared to thrift banks.Â  Â Relative to technology, online feedback is the most common component in the banksâ€™ website while link to homepage is the most usual user support feature relative to the bankâ€™s financial reporting practice. Lastly, asset size and bank type were found to have a high significant relationship with the extent of IFR.